2018
DOI: 10.1111/jon.12497
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Kurtosis Imaging Shows Similar Cerebral Axonal Damage in Patients with HIV Infection and Multiple Sclerosis

Abstract: We conclude that DKI-derived WMTI metrics may be a valuable tool in assessing the WM changes of medically complex HIV-infected individuals. While not powered to examine potential etiologies of WM changes in this pilot sample, regional variations in WMTI metrics were seen. When contrasted with changes consequent to chronic MS of similar duration, HIV and its comorbidities appear to result in similar degrees of axonal damage, but regionally variable amounts of myelin loss and extraxonal abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The above findings along with the observation of a strong positive correlation between HIV vDNA+ cells in the CC and GDS in virally suppressed subjects with HAND may suggest a potential role of HIV in the brain in the development of neurocognitive impairments despite suppressive long-term HAART. Brain imaging studies of HAART treated HIV patients have previously shown selective white matter disease (Garvey et al 2014; Ragin et al 2015; Randall et al 2017; Buyukturkoglu et al 2018) and a correlation between loss of CC integrity with neurocognitive deficits (Wu et al 2006; Kelly et al 2014). However, it is still unclear whether the neurocognitive impairment in the era of HAART is due to ART neurotoxicity or HIV induced neuroinflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…The above findings along with the observation of a strong positive correlation between HIV vDNA+ cells in the CC and GDS in virally suppressed subjects with HAND may suggest a potential role of HIV in the brain in the development of neurocognitive impairments despite suppressive long-term HAART. Brain imaging studies of HAART treated HIV patients have previously shown selective white matter disease (Garvey et al 2014; Ragin et al 2015; Randall et al 2017; Buyukturkoglu et al 2018) and a correlation between loss of CC integrity with neurocognitive deficits (Wu et al 2006; Kelly et al 2014). However, it is still unclear whether the neurocognitive impairment in the era of HAART is due to ART neurotoxicity or HIV induced neuroinflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…DKI allows for the quantification of white matter tract integrity (WMTI), providing markers of intra‐axonal damage, axonal loss, extracellular inflammation, gliosis and demyelination . DKI‐derived metrics have been applied in several neurological disorders , providing increased sensitivity and specificity in detecting pathological changes .…”
Section: Introductionmentioning
confidence: 99%
“…Also, a recent study employed TBSS to compare normal appearing WM between HIV‐infected patients and multiple sclerosis patients to study associations between cognitive scores and WM tract integrity in two regions of interest (ROI) placed in the corpus callosum and ATR. While in our study, we employed a whole‐brain approach to correlational investigations, the ATR is comprised within the regions in which we found statistically significant associations between biochemical and DTI‐DKI metrics in the ATR . Also, this previous study did not exclude patients with coinfections, hence, introducing potential confounds which could have decreased the sensitivity of ROI‐wise correlational tests.…”
Section: Discussionmentioning
confidence: 98%
“…Also, this previous study did not exclude patients with coinfections, hence, introducing potential confounds which could have decreased the sensitivity of ROI‐wise correlational tests. While these finding could offer support for understanding physiopathological mechanism underlying the neurocognitive impairment of HIV patients, the pathogenesis of HIV‐related brain alterations remains in part unclear.…”
Section: Discussionmentioning
confidence: 99%